Symptoms of depression in children part of the “snowflake” generation and their input for the functioning of the whole family. Narrative research of modern families - Zalewska, Sabina (Forum pedagogiczne, 2022)
In the article I analyze the problem of mental health about children of the generation of "snowflakes". The subject of the article is the problem of child depression affecting the whole family system. The main symptoms of this disease are presented. They are discussed in detail with their impact on family relationships. The main functions of the family were recalled, as they gave the structure for the analysis of narrative tests. A lot of attention was paid to the description of the impact of depression on the life of the whole family, including marriage, contact with children, social contacts, changes in the family's activity and material situation, as well as emotional reactions of family members. The analysis of narrative tests shows the family's reactions to the child's disease.